TINJAUAN FIKIH MUAMALAH TERHADAP PRAKTIK SHORT SELLING DAN MARGIN TRADING DI PASAR MODAL KONVENSIONAL SEBAGAI REFLEKSI PENGUATAN PASAR MODAL SYARIAH - Budiman Budiman; Deden Hidayat; Yayah Rukhayah; Amelia (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2026)
Short selling and margin trading enhance liquidity in conventional markets but trigger volatility and disadvantage retail investors. This study critically analyzes their operational mechanisms from contemporary Fiqh Muamalah perspectives to strengthen Indonesia's Shariah Online Trading System (SOTS) architecture. Using a descriptive-qualitative method with a legal-normative approach, secondary data from DSN-MUI fatwas, OJK regulations, and Islamic jurisprudence were analyzed via content and comparative techniques. The results indicate that short selling features structural Sharia flaws, categorized as bai' al-ma'dum and violating qabdh, which introduces gharar and maysir. Meanwhile, margin trading constitutes riba al-qardh due to commercial interest on leverage. Conclusively, these prohibitions are effectively integrated into SOTS through systemic barriers: automatically rejecting zero-balance short sales and enforcing a Cash Advanced Market. This offers crucial insights for regulators designing resilient Islamic capital market roadmaps.